The effect of the distance between two bulk carriers on the ship-ship interaction during the overtaking process - Joureh, Nawar (Latakia University Journal -Engineering Sciences Series, 2025)
The hydrodynamic interaction between two or more ships in ports or inland waterways is a very important research area in marine engineering. During ship maneuvering, the ship captain tries to determine the speed limit and distance between their ship and any other ship passing by, especially in narrow waterways. This requires accurate prediction of the interaction force acting on both ships. Experimental studies have shown that the interaction can lead to a very large transversal forces and these forces are highly time-dependent, which may cause ships to deviate from their original courses during the overtaking process, leading to collisions. Based on the results of experimental measurements, some empirical formulas have been proposed that provide an approximate estimate of the forces acting on ships during the overtaking process, but their results are satisfactory only when the ship speed is very high, and the water depth is shallow and constant. Currently, the Computational Fluid Dynamics (CFD) technique is considered one of the best and most accurate techniques used worldwide to study and calculate all phenomena related to fluids. Accordingly, in this research, the URANS (Unsteady RANS Averaged Navier Stocks Equation) equations and the k-Ꞷ SST turbulence model were used to solve the Navier-Stokes equations. Then, CFD was used to calculate the hydrodynamic interaction between two JBC bulk ships with different values ​​of the transverse distance between the two ships. The interaction between the two ships was studied with different values ​​of the distance between them . At first, a validation study was carried out for the numerical grid and settings by comparing the CFD-results obtained with the available experimental results, and the agreement was very good. The CFD-results confirm that the transverse distance between the two ships greatly affects the interaction between them, and the smaller the distance, the greater the probability of the two ships colliding with each other.